Demographic Factor, Self-Esteem and Resistance to Change: A study on Resistance to Change Among Administrative Staff in the International Islamic University Malaysia (IIUM) - Nik Hziman, Nik Mat (2011)
This study focuses on a major issue in the field of organizational change, which is resistance. The aim of the study is to investigate the correlation of self-esteem and demographic factor i.e. age, gender, educational qualification and length of work experience as contributing factors affecting resistance to change. This analysis has impact to the direction and strength of the resistance factor. Two hundred and forty four (240) questionnaires were distributed to the respective office i.e. Management Services Division, Finance Division, Student Affairs Division and Student development Division and 116 respondents collected among IIUM administrative staff to measure the levels of self-esteem and demographic factors comparatively with resistance to organizational change using statistical techniques such as ANOVAs, Chi-squares, factor analysis and regression. Results of the study showed that there was a positive correlation between self-esteem and resistance, and on the part of demographic factors only high academic qualification showed a positive correlation while the rest of the factors did not show any correlation. These result will be able to help IIUM specifically and organizations at large on how to manage and handle “resistance to change”.